Social movement de-radicalisation and the decline of terrorism the morphogenesis of the Irish Republican movement - Clubb, Gordon (Contemporary terrorism studies, 2017)
By drawing on social movement theories, this book explains how terrorist movements decline, using the case of Irish Republicanism. The fundamental aim of the book is to provide theoretical and conceptual insights into how terrorism can not only come to an end, but can be prevented from emerging to be a significant threat again within a society. This book will be of much interest to students of terrorism and political violence, social movement theory, British and Irish Politics, war and conflict studies, security studies and IR in general.